2021
DOI: 10.1097/gox.0000000000003477
|View full text |Cite|
|
Sign up to set email alerts
|

Regret after Gender-affirmation Surgery: A Systematic Review and Meta-analysis of Prevalence

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
68
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(74 citation statements)
references
References 45 publications
3
68
0
3
Order By: Relevance
“…In terms of detransition rates, one meta-analysis reports rates of less than one percent [ 50 ] but the primary studies are inherently flawed by loss to follow up. A recent UK GIC case note review found a detransition rate of 6.9% [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…In terms of detransition rates, one meta-analysis reports rates of less than one percent [ 50 ] but the primary studies are inherently flawed by loss to follow up. A recent UK GIC case note review found a detransition rate of 6.9% [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Penile inversion vaginoplasty is the gold standard surgical technique of feminizing genital surgery (Bizic et al, 2014;Horbach et al, 2015;Buncamper et al, 2016;Dreher et al, 2018;Bustos et al, 2021;Moises da Silva et al, 2021). This surgery was first introduced in the early 1900's and has undergone various permutations in search of the optimal outcome (Horbach et al, 2015).…”
Section: Vaginoplasty and The Neovaginal Epitheliummentioning
confidence: 99%
“…Bustos et al 1 aimed to measure the prevalence of regret following gender-affirmation surgery. Given the significant rise in young people seeking medical intervention for gender dysphoria, which can include surgery, outcome studies that accurately assess regret are of increasing importance.…”
Section: Sirmentioning
confidence: 99%
“…Bustos et al 1 acknowledge “moderate-to-high risk of bias in some studies.” Actually, this affects 23 of the 27 studies. The majority of included studies ranged between “poor” and “fair” quality: only five studies—representing just 3% (174) of total participants—received higher quality ratings.…”
Section: Sirmentioning
confidence: 99%